IMPLEMENTASI PENGEMBANGAN SISTEM JARINGAN INTERNET PT. INKA MULTI SOLUSI SERVICE BERBASIS ROUTER MIKROTIK - Herawan, Rifky Mina; Prihantoro, Cahyo (UNIVERSITAS STEKOM, 2024)
The high usage of internet networks, coupled with various direct and indirect attacks, will affect the activities on the internet network. The office of PT. INKA Multi Solusi Service, located in Madiun City, has each employee working with their own computers, and the office's internet speed is 150 Mbps. However, the internet network at PT. INKA Multi Solusi Service faces several optimization issues. Three of these issues are related to internet security login, bandwidth conflicts, and unrestricted website access, leading to virus-related problems. The proposed solution involves implementing the Hierarchical Token Bucket (HTB) method, a bandwidth management technique used to control internet networks. HTB operates by allocating bandwidth hierarchically based on user needs. One of its advantages is that any unused bandwidth will be reallocated according to the priority needs of each user in a network. A captive portal will be implemented to protect the network from unauthorized users, ensuring that users have been granted permission to access the network through a username and password. Web filtering will safeguard internet users from harmful websites and restrict access to specific websites, especially those that could be potential sources of network viruses.